2006
DOI: 10.1016/j.rmed.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and health status after hospitalisation for COPD: A multicentre study in the Nordic countries

Abstract: Patients with chronic obstructive pulmonary disease (COPD) often report anxiety, depression and poor health status, not least if they experience repeated hospitalisations due to acute exacerbations. The aim of this study was to analyse the interrelationships between health status, anxiety, depression and physical status in COPD patients being discharged after hospitalisation. This was a prospective study of 416 patients in five university hospitals in each of the Nordic countries. Data included demographic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 21 publications
13
143
3
6
Order By: Relevance
“…This was in contrary with the fi ndings from the other study on anxiety and depression among hospitalized COPD patients in Nepal where they only found a slightly higher occurrence among females 8 . The fi nding in the current study was though consistent with the fi ndings from a hospital based study in Italy among COPD patients attending respiratory unit which showed 38% of female participants with anxiety 6 and another study from Nordic countries among patients at the time of discharge after hospitalization showing 47% of women having anxiety compared to 34% in men 18 . Higher proportion of separated/widowed/divorced participants had anxiety as well as depression in the current study which might be due to reasons such as lack of husband's support.…”
Section: Discussionsupporting
confidence: 91%
“…This was in contrary with the fi ndings from the other study on anxiety and depression among hospitalized COPD patients in Nepal where they only found a slightly higher occurrence among females 8 . The fi nding in the current study was though consistent with the fi ndings from a hospital based study in Italy among COPD patients attending respiratory unit which showed 38% of female participants with anxiety 6 and another study from Nordic countries among patients at the time of discharge after hospitalization showing 47% of women having anxiety compared to 34% in men 18 . Higher proportion of separated/widowed/divorced participants had anxiety as well as depression in the current study which might be due to reasons such as lack of husband's support.…”
Section: Discussionsupporting
confidence: 91%
“…Elevated anxiety in COPD patients is more common in current smokers than in nonsmokers. 43 Smoking is a common reason to explain the high association of anxiety with COPD. Tobacco use is widely acknowledged as the single most important environmental risk factor for the development of COPD, 28 and a high level of anxiety is a risk factor for starting to smoke.…”
Section: Discussionmentioning
confidence: 99%
“…(74% w wieku ≥ 65 lat), określono częstość występowania chorób sercowo-naczyniowych, która była znamiennie wyższa u tych pacjentów w porównaniu z grupą kontrolną bez POChP. Wśród patologii sercowo-naczyniowych najczę-ściej stwierdzono zatorowość płucną 5,46 [12]. W innym badaniu zauważono, że chorzy na POChP mają ponad dwukrotnie wyższe ryzyko względne wystąpienia zawału serca w ciągu pierwszych 5 dni i 1,26 raza wyższe ryzyko udaru mózgu w czasie 49 dni od epizodu zaostrzenia choroby obturacyjnej [13].…”
Section: Choroby Sercowo-naczyniowe a Pochpunclassified